2007
DOI: 10.1134/s0012500807100059
|View full text |Cite
|
Sign up to set email alerts
|

Study of alkaloids of the flora of Siberia and Altai: Synthesis of bivalent ligands of the aconitane type

Abstract: A method for N-deeH~ylalion ofditerpene alkaloids of the aconicane type by the Cope reaction was developed using conversions of lappacomthm and elatine as examples. The previously unknown hi:tones of N-deethyla~ed tappaconifine, daline, and elatidine were prepared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previously, we successfully synthesized lappaconitine ynones 5, 6 by the employment of transition-metal-catalyzed cross-coupling reactions of 5 -ethynyllappaconitine 2 [39] with benzoic acid chlorides 3, 4 under Sonogashira cross-coupling reaction (Scheme 1) [38]. We observed that compounds 5 could be almost quantitatively converted into 2,4,6-trisubstituted pyrimidines 7, 8 by refluxing with acetamidine hydrochloride 9 or guanidine hydrocarbonate 10 in acetonitrile in the presence of Na 2 CO 3 (2 equivalent) with the isolated yield 81-95%.…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we successfully synthesized lappaconitine ynones 5, 6 by the employment of transition-metal-catalyzed cross-coupling reactions of 5 -ethynyllappaconitine 2 [39] with benzoic acid chlorides 3, 4 under Sonogashira cross-coupling reaction (Scheme 1) [38]. We observed that compounds 5 could be almost quantitatively converted into 2,4,6-trisubstituted pyrimidines 7, 8 by refluxing with acetamidine hydrochloride 9 or guanidine hydrocarbonate 10 in acetonitrile in the presence of Na 2 CO 3 (2 equivalent) with the isolated yield 81-95%.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Oxygen or water sensitive reactions were performed under the argon atmosphere. The starting material: 5 -ethynyllappaconitine 2 [39], 5 -iodolappaconitine 17 [45] and Ad 2 PBn • HBr [54,55] were synthesized, according to previously published procedures. Other reagents were purchased from commercial sources and were used without further purification.…”
Section: General Informationmentioning
confidence: 99%
“…4) was the second example where the participation of electron transfer stage in the process of ligand-receptor interaction was suggested and confirmed using physicochemical approach [61]. It is known that lappaconitine reveals bradycardic and hypotensive activity [64][65]. It was demonstrated using CIDNP technique, that in the presence of amino acids tyrosine and tryptophan the reaction occurs via formation of intermediate lappaconitine radical anion with following proton transfer and ether C(O)O-R bond cleavage.…”
Section: Lappaconitine Complex With Glycyr-rhizic Acidmentioning
confidence: 99%
“…This results in the drop of the product yield and, in turn, might prolong the therapeutic action of the drug. It should be mentioned that high photosensitivity of NF [64] and formation of free radical intermediates [60] [GA], mM be the reasons of high phototoxicity of nifedipine. The using of GA complexes of NF instead of free NF will results in significant decrease of toxicity of this drug, including phototoxicity (from both, reducing therapeutic dose and reducing reactivity).…”
Section: Interaction Of Nifedipine-glycyrrhizin Complex With Amino Acmentioning
confidence: 99%
“…The known compound 18 [32] was involved into the cross‐coupling reaction with benzoic acid chlorides 8 a – f in the presence of a catalytic amount of Pd(PPh 3 ) 2 Cl 2 (1 mol%), CuI (2 mol%), PPh 3 (2 mol%), and Et 3 N as the base by heating in benzene (65 °C, 7 h) (TLC‐control), then the solvent was evaporated and acetonitrile, hydroxylamine hydrochloride (1.2 equiv. ), and sodium carbonate (3 equiv) (conditions i ) were added (Table 2).…”
Section: Resultsmentioning
confidence: 99%